2013
DOI: 10.1073/pnas.1312200110
|View full text |Cite
|
Sign up to set email alerts
|

Observation of orientation-dependent electron transfer in molecule–surface collisions

Abstract: Molecules typically must point in specific relative directions to participate efficiently in energy transfer and reactions. For example, Förster energy transfer favors specific relative directions of each molecule's transition dipole [Förster T (1948) Ann Phys 2(1-2):55-75] and electron transfer between gas-phase molecules often depends on the relative orientation of orbitals [Brooks PR, et al. (2007) J Am Chem Soc 129(50):15572-15580]. Surface chemical reactions can be many orders of magnitude faster than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
81
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(90 citation statements)
references
References 42 publications
(54 reference statements)
6
81
0
3
Order By: Relevance
“…It has been shown that electron transfer is an important part of the electronically nonadiabatic dynamics in this system. 26,44 It is believed that DFT may describe electron transfer inadequately in molecular interactions at metal surfaces. 45 Hence a more fundamental, but also more elaborate, improvement would be to replace the DFT calculation by more advanced methods such as quantum mechanical embedding theory, which allows a true ab initio description of the system.…”
Section: Suggestions For Improvements To the Theoretical Modelmentioning
confidence: 99%
“…It has been shown that electron transfer is an important part of the electronically nonadiabatic dynamics in this system. 26,44 It is believed that DFT may describe electron transfer inadequately in molecular interactions at metal surfaces. 45 Hence a more fundamental, but also more elaborate, improvement would be to replace the DFT calculation by more advanced methods such as quantum mechanical embedding theory, which allows a true ab initio description of the system.…”
Section: Suggestions For Improvements To the Theoretical Modelmentioning
confidence: 99%
“…1 in Ref. 15. The average angle (expectation value <Θ>) between electric field lines (which means surface normal for the employed experimental setup geometry) and dipole moment (bond axis) is 68…”
Section: B Production Of Oriented No Moleculesmentioning
confidence: 99%
“…15 Due to increased attraction when approaching the surface with the N-atom first, the NO molecules can approach the surface more closely than for configurations with the O-atom first. This results in more efficient electron transfer from the surface to the NO molecule-forming transient NO − -an event which is essential to the electronically nonadiabatic vibrational relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the relevance of this dissipation channel in gas-surface interactions that involve energies up to a few eV is not so clear. It depends not only on the specific system, but also on the elementary process considered, as shown by different studies on scattering [5][6][7][8][9][10][11][12] and adsorption [6,[13][14][15][16][17][18][19][20][21][22][23][24][25][26] of atoms and molecules on surfaces. Low-energy e-h pair excitations have been detected as chemicurrents on Schottky diode devices during the chemisorption of atomic and molecular species on metals [13][14][15].…”
mentioning
confidence: 99%